Development and evaluation of a recombinant antigen-based indirect immunofluorescence assay for the diagnosis of Lassa fever - Moolla, Naazneen (University of Pretoria, 2022)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2022.